Realism as Protest: Kluge, Schlingensief, Haneke - Forrest, Tara (transcript, 2015)
Realism as Protest draws on the »realistic method« developed by Alexander Kluge to counter the limited image of reality generated by the mainstream media. Focusing on innovative productions produced by Kluge, Schlingensief and Haneke, this groundbreaking study explores how the experimental form of their work in film, television and theatre facilitates thinking, discussion and debate about the possibilities for cultural and political change.